POEMS syndrome presenting with Vibrio vulnificus–like cutaneous lesions: a CARE guidelines-compliant case report - Li, Xiaomei; Lin, Bihong; Lin, Liping; Song, Conghua (Frontiers in Medicine, 2025)
BackgroundPOEMS (Polyneuropathy, Organomegaly, Endocrinopathy, Monoclonal plasma cell disorder, Skin changes) syndrome is a rare paraneoplastic disorder driven by a λ-restricted plasma cell clone. Cutaneous manifestations are common but typically limited to hyperpigmentation, hemangiomas, and sclerodermoid changes. We herein report the first case of POEMS syndrome presenting with skin lesions closely resembling those of Vibrio vulnificus infection.Case presentationA 65-year-old woman was admitted with malignant hypertension, refractory ascites, symmetrical thigh ecchymoses evolving into tense hemorrhagic bullae, and progressive sensorimotor polyneuropathy. Laboratory workup revealed thrombocytosis, hypoalbuminemia, acute kidney injury, an IgA-λ monoclonal band on serum immunofixation, and a markedly elevated VEGF level (729.7 pg./mL, reference range: 9–86 pg./mL). Electromyography confirmed a demyelinating neuropathy. Infectious, autoimmune, hepatic, renal, and malignant etiologies were systematically excluded. A multidisciplinary team reached the diagnosis of POEMS syndrome based on two mandatory criteria (polyneuropathy and monoclonal plasma cell disorder), one major criterion (elevated VEGF), and multiple minor criteria (extravascular volume overload, endocrinopathy, skin changes, thrombocytosis, organomegaly).Management and outcomeThe patient received bortezomib plus dexamethasone, leading to gradual resolution of skin lesions, improvement of neuropathic symptoms, and reduction of VEGF levels. After six cycles, ascites resolved and neurological function partially recovered.ConclusionThis case expands the spectrum of POEMS-associated skin changes to include V. vulnificus–like bullous lesions. “V. vulnificus–like” refers purely to morphological similarity and not microbiological confirmation. Awareness of such atypical presentations is essential for early recognition. Clinicians should consider POEMS syndrome in patients with unexplained multisystem involvement and vascular skin changes. VEGF measurement and immunofixation electrophoresis are essential tools for timely diagnosis.